Hubungan antara Riwayat Paparan Asap Rokok dengan Kejadian Ketuban Pecah Dini pada Ibu Hamil di RSUD Dr. H. Soewondo Kendal - Muntoha, Muntoha; Suhartono, Suhartono; Wahyuningsih, Nur Endah (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background : The incidence of maternal mortality were caused by bleeding, eclampsia, bleeding before labor and infection. One of the triggering factors caused the onset of infection was premature rupture (PR). It defined as the rupture of amniotic membrane without uterus contractions and labor signs. The strength of amniotic membrane could also be disrupted due to the effect of nicotine of cigarette. The nicotine contained in cigarette was harmful to the pregnancies. The premature rupture rate in Indonesia was quite high. In Kendal regency the number of pregnant women who experienced in premature rupture in the year 2011 was approximately 445 patients. Meanwhile, in January up to September 2012 the premature rupture cases reached about 542 patients. Based on the preliminary survey conducted on 7 premature rupture patients in dr.H.Soewondo hospital Kendal in October 2012 the data obtained 5 (71,4%) patients had a history of smoking husbands. Methode : This study purposed to know the most influential variable to the incidents of premature rupture in pregnant women in dr.H.Soewondo Kendal, Central Java Province. The design of the study used case control. The case population was pregnant women with premature rupture. Meanwhile, the control population of normal pregnant women and the sampling technique used accidental sampling. The collecting data used questionnaire, checklist and tool, rapid diagnostic cotinine test. The data analysis used chi square test. Result : The result of the study showed the most influential variable to the incidents of premature rupture was the history of cigarette smoke exposure with value p = 0,00 and OR 23,188. Thus, it could be concluded that the history of cigarette smoke exposure was the most influential variable to the incidents of the premature rupture than parity and polyhidramnion history. KeywordsÂ  : the cigarette smoke exposure, premature rupture, cotinine, polyhidramnion.